Manifestasi Pragmatisme Pendidikan Politik (Analisis Resepsi pada Komodifikasi Berita Selebriti Politisi) - Wahyuni Choiriyati (LUGAS Jurnal Komunikasi, 2017)
Celebrity politicians and mass media attract public’s attention. News about celebrity politicians become a commodity for mass media and it increases the popularity of the celebrity politicians. This creates relationships of capitalism motion in mass media that has penetrated digital media. Focus of this study is public meanings about celebrity politicians on online media. Using qualitative methods and in-depth interviews, this study shows how the practice of the commodification content of celebrity politicians and mass media was interwoven. The result also shows that the practice of the commodification of online media content in the fabric of pragmatism has no exercise of political education efforts through the media. Media were supposed to carry out their duties in an effort to educate the public actually shirking its duty. Practice capitalism in media shallow public thinking on the political dynamics in Indonesia. The struggle between the interests of the media as an institution of political education and vice versa become imaging agents on the political role. This siltation is the embryo of the normalization of news construction power that led towards pragmatism.